The Effect of Concealing the Results of Laboratory Analyzes on the Rulings “Infertility as a Model” a Medical Jurisprudential Study (Islamic Sciences Journal, 2023)
ABSTRACT                    Laboratory analysis of blood and other body fluids plays an essential role in the diagnosis and treatment of diseases. Therefore, our research was under the title (The effect of concealing the results of laboratory analyzes on judgments of “sterility as a model” - a medical jurisprudential study-), and the medical analysis specialist currently occupies senior positions in clinical medical laboratories, .The medical laboratory specialist is a health professional with experience in medical laboratories and is responsible for Giving accurate and logical information for laboratory experiments and analyzes that help in the diagnosis and treatment of diseases, as well as monitoring the general condition of the patient. We can see the impact of the future of advanced medical tests and its role in diagnosing health problems such as cancer resulting from birth defects, infertility cases and other diseases. Infertility is one of the biggest problems facing couples, especially in our Arab society, which the husband strongly desires to have children as well as the wife. The research included an introduction, four sections, and a conclusion, as for the first topic: a historical overview of medical laboratories, the second: the definition and legitimacy of laboratory analyzes, and the third: the importance of laboratory analyzes, and concealment and disclosure of medical secrets, fourth: practical issues in the effect of concealing the results of laboratory analyzes in Judgments, then conclusion: it included the most important results that it reached.